Human Resources, Work Culture, Leadership and Infrastructure as Aspects of Readiness for Implementing Electronic Medical Records in Dental and Oral Hospital - Lareshya, Brilianti Haditya; Girsang, Ermi; Nasution, Sri Lestari Ramadhani (FORIKES, 2025)
Electronic medical records play a crucial role in the efficiency, accuracy, and quality of service, so its implementation requires readiness from various aspects. This study aimed to analyze the readiness of electronic medical records implementation at Dental and Oral Hospital of the University of North Sumatera based on four main aspects: human resources, organizational work culture, leadership governance, and information technology infrastructure. The study was conducted at Dental and Oral Hospital of the University of North Sumatera from November to December 2024 with a quantitative analytical approach using a cross-sectional design. A sample of 71 people was selected through purposive sampling, consisting of healthcare and non-healthcare workers directly involved with the electronic medical records system. The research instrument used a questionnaire based on the DOQ-IT method and was analyzed using SmartPLS. The results showed that the readiness for implementing electronic medical records at Dental and Oral Hospital of the University of North Sumatera was in the